Sinergitas Komite Sekolah Dengan Lembaga Usaha Dalam Meningkatkan Pelayanan di Sekolah Dasar - Novi Yanti; Yetri Yetri; Andi Thahir (Institut Agama Islam Negeri Palopo, 2022)
The purpose of this study was to determine the role of school committee synergy in building a pattern of cooperation between business institutions and SDN 1 Penengahan Bandar Lampung City. The research method used in this research is descriptive qualitative method. Data collection techniques and procedures were obtained from observation sheets, field notes, interviews, and documentation. Qualitative data analysis was carried out in four stages, namely data reduction, data display, and conclusing drawing or verificatioThe purpose of this study was to determine the role of school committee synergy in building a pattern of cooperation between business institutions and SDN 1 Penengahan Bandar Lampung City. The research method used in this research is descriptive qualitative method. Data collection techniques and procedures were obtained from observation sheets, field notes, interviews, and documentation. Qualitative data analysis was carried out in three stages, namely data reduction, data display, and conclusing drawing or verification. The results of this study indicate that 1) the school committee has developed a pattern of cooperation between SDN 1 Penengahan Bandar Lampung City and CSR from PT. KAI in partnership and community development programs; 2) The synergistic role of the school committee as a mediator in building cooperation between PT KAI and SDN 1 Penengahan Bandar Lampung City is very important in realizing partnership and community development programsn. The results of this study indicate that 1) the school committee has developed a pattern of cooperation between SDN 1 Penengahan Bandar Lampung City and CSR from PT. KAI in partnership and community development programs; 2) The synergistic role of the school committee as a mediator in building cooperation between PT KAI and SDN 1 Penengahan Bandar Lampung City is very important in realizing partnership and community development programs.